Trichobezoar in the absence of trichotillomania: a consequence of occupational hazard - Jain, Rajiv; Mahor, Devendra (International Surgery Journal, 2016)
Trichobezoars are concretions of hair, which accumulate in the gastrointestinal tract. Trichotillomania is a psychiatric illness with compulsive desire to pull out ones hair. Trichobezoars are rarely described in the absence of trichotillomania. We report a case of trichobezoar associated with trichophagia in the absence of trichotillomania. An 18 year old thin built girl presented with complaints of pain in abdomen and upper abdominal fullness with loss of appetite and weight loss for the last 2 months. Ultrasound abdomen and upper gastrointestinal endoscopy were suggestive of gastric bezoars. Exploration of history revealed that the patient works as a hairstylist. However, she denied of pulling her own hairs. Physical examination of scalp and other body parts did not show any evidence of alopecia or pulling of hair/short hair. She was managed surgically and was counseled about the consequences of eating hairs and was discouraged from eating hair. The absence of trichotillomania should not be considered as absence of trichophagia and sometime the occupational history of the patient can be helpful in leading to the diagnosis.